RETRACTED: CXCL6 Promotes Renal Interstitial Fibrosis in Diabetic Nephropathy by Activating JAK/STAT3 Signaling Pathway - Sun, Meng-Yao; Wang, Su-Juan; Li, Xiao-Qin; Shen, Yu-Li; Lu, Jian-Rao; Tian, Xin-Hui; Rahman, Khalid; Zhang, Li-Jun; Nian, Hua; Zhang, Hong (Frontiers in Pharmacology, 2019)
In this study the role of CXCL6 in diabetic nephropathy (DN) was investigated. It was found to be overexpression in DN patients and DN rat model. And the expression of fibrosis-related cytokines was consistent with the expression of CXCL6. High glucose significantly increased the proliferation of rat renal fibroblasts NRK-49F cell and the expression of CXCL6. Knockdown of CXCL6 ameliorated the pro-proliferation effect of high glucose and decreased the expression of fibrosis-related cytokines, while CXCL6 overexpression exhibited the opposite phenomenon. Gene set enrichment analysis, Western blot and ELISA showed that Janus kinase-signal transducer and activator of transcription (JAK-STAT) and CYTOKINE_CYTOKINE_RECEPTOR_INTERACTION signaling pathways were correlative with CXCL6. This data indicates that CXCL6 may promote fibrosis-related factors to accelerate the development of diabetic nephropathy renal interstitial fibrosis by activating JAK/STAT3 signaling pathway. CXCL6 is promising to be a potential novel therapeutic target and candidate biomarker for JAK/STAT3 signaling for the treatment of DN.